Fitted computational method for singularly perturbed convection-diffusion equation with time delay - Tesfaye, Sisay Ketema; Duressa, Gemechis File; Woldaregay, Mesfin Mekuria; Dinka, Tekle Gemechu (Frontiers in Applied Mathematics and Statistics, 2023)
A uniformly convergent numerical scheme is proposed to solve a singularly perturbed convectiondiffusion problem with a large time delay. The diffusion term of the problem is multiplied by a perturbation parameter, ε. For a small ε, the problem exhibits a boundary layer, which makes it challenging to solve it analytically or using standard numerical methods. As a result, the backward Euler scheme is applied in the temporal direction. Non-symmetric finite difference schemes are applied for approximating the first-order derivative terms, and higher-order finite difference method is applied for approximating the second-order derivative term. Furthermore, an exponential fitting factor is computed and induced in the difference scheme to handle the effect of the small parameter. Using the discrete maximum principle, the stability of the scheme is examined and analyzed. The developed scheme is parameter-uniform with a linear order of convergence in both space and time. To examine the accuracy of the method, two model examples are considered.Further, the boundary layer behavior of the solutions is given graphically.